2022
DOI: 10.3390/children9020246
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of SARS-CoV-2 IgG Seroprevalence in Children and Factors Associated with Seroconversion: Results from a Multiple Time-Points Study in Friuli-Venezia Giulia Region, Italy

Abstract: Data on the effective burden of the SARS-CoV-2 pandemic in the pediatric population are limited. We aimed at assessing the prevalence of SARS-CoV-2 IgG antibodies in children at three subsequent time-points. The study was conducted between January 2021 and July 2021 among children referring to the Research Institute for Maternal and Child Health “Burlo Garofolo” in Trieste, a referral regional hospital in Friuli Venezia Giulia, Italy. A multivariate analysis was conducted to assess factors independently associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
1
5
3
Order By: Relevance
“…This result indicates that at least one in three unvaccinated children had acquired either symptomatic or asymptomatic COVID-19 infection within 18 months of the pandemic due to the presence of positive antibodies. The overall seroprevalence rate of SARS-CoV-2 among children in this study was higher than in other studies [13][14][15][16]19]. These previous studies showed a prevalence of 1.3% in Northern Cyprus [12], 5.8% among school-and preschool-age children in Canada [13], 9.5% to 15.4 (for IgG) in Italy [14,15], 27.1% in Saudi Arabia [19], and 25.3% in Brazil [16].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This result indicates that at least one in three unvaccinated children had acquired either symptomatic or asymptomatic COVID-19 infection within 18 months of the pandemic due to the presence of positive antibodies. The overall seroprevalence rate of SARS-CoV-2 among children in this study was higher than in other studies [13][14][15][16]19]. These previous studies showed a prevalence of 1.3% in Northern Cyprus [12], 5.8% among school-and preschool-age children in Canada [13], 9.5% to 15.4 (for IgG) in Italy [14,15], 27.1% in Saudi Arabia [19], and 25.3% in Brazil [16].…”
Section: Discussioncontrasting
confidence: 65%
“…There have been some studies that examined the presence of antibodies among children. These previous studies reported different seroprevalence values, ranging from a low value of 1.3% in Northern Cyprus [12] to 5.8% among school-and preschool-age children in Canada [13], 9.5% and 15.4% (for IgG) in Italy [14,15], and a high of 25.3% in Brazil [16]. Further seroprevalence studies among children in diverse geographic locations can provide additional details on SARS-CoV-2 infection among children.…”
Section: Introductionmentioning
confidence: 96%
“…Vulnerable pupils and those from lower SES schools were more at risk to test positive in our study. Similar findings were reported for schoolchildren belonging to racial and ethnic minorities in Canada [ 19 ], Italian children with foreign citizenship [ 24 ], and in low SES families in German schools [ 21 ]. Crowding and limited options to isolate were formulated as plausible causes, but neither we nor Zinszer et al observed an increased risk for seropositivity in larger families or in children who shared bedrooms.…”
Section: Discussionsupporting
confidence: 82%
“…In England and elsewhere, opportunistic testing of residual sera from children having blood tests, in hospital, for example, has been used to assess SARS-CoV-2 antibody prevalence in children but these are prone to multiple biases, especially representativeness to the general population. 24 , 25 , 26 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%